4-Benzyloxylonchocarpin and Muracatanes A-C from Ranunculus muricatus L. and Their Biological Effects - Hidayat Hussain; Iftikhar Ali; Daijie Wang; Nilufar Z. Mamadalieva; Wahid Hussain; René Csuk; Anne Loesche; Lucie Fischer; Dan Staerk; Syariful Anam; Mashail N. AlZain; Maria Mushtaq; et al. (Biomolecules, 2020)
Ranunculus muricatus L. is a spiny fruit buttercup that is used in various traditional medicinal systems. In the current investigation of R. muricatus, the new chalcone 4-benzyloxylonchocarpin (1), the new anthraquinone muracatanes A (2), the new-to-nature anthraquinone muracatanes B (3), and the new naphthalene analog muracatanes C (4) were isolated, in addition to the three previously reported compounds, 4-methoxylonchocarpin (5), β-sitosterol (6), and β-sitosterol β-D-glucopyranoside (7). Their structures were elucidated using 1D (1H and 13C) and 2D (COSY, HSQC, and HMBC) NMR spectroscopy and HR-ESI-MS. Chalcone 1 showed potent acetylcholinesterase inhibitory effects with Ki of 5.39 µM and Ki′ of 3.54 µM, but none of the isolated compounds showed inhibitory activity towards butyrylcholinesterase. Anthraquinone 3 illustrated α-glucosidase inhibitory effects with IC50-values of 164.46 ± 83.04 µM. Compound 5 displayed moderate cytotoxic activity towards ovarian carcinoma (A2780, IC50 = 25.4 µM), colorectal adenocarcinoma (HT29, IC50 = 20.2 µM), breast cancer (MCF7, IC50 = 23.7 µM), and thyroid carcinoma (SW1736, IC50 = 26.2 µM) while it was inactive towards pharynx carcinoma (FaDu: IC50 > 30 µM).